2011
DOI: 10.1080/21615667.2011.10878935
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Profile Evaluation Through Lactate and Heart Rate in National Level Greco-Roman Wrestlers

Abstract: The purpose of this study was to evaluate the physiological profile of top-level wrestlers in a simulated competition. 12 male athletes, aged 23.2±4.5yrs who were participants in the 74kg division at the Greece National Greco-Roman Championship were the evaluated subjects. During all competitions the heart rates were measured and stored with a transmitter with a digital display while the capillary blood samples were collected 3 minutes after each round was completed in order to evaluate the lactate concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…In this condition, the authors observed that matches had an energetic cost of approximately 181 kJ. As well as observed in karate matches [14,43], it was observed a predominance of the oxidative system (66%). When energy systems contribution was presented by each round it was observed an increase over time with an absolute oxidative contribution in round 1 (98 ± 15 kJ) lower than in rounds 2 (127 ± 14 kJ) and 3 (134 ± 18 kJ).…”
Section: Taekwondosupporting
confidence: 52%
See 2 more Smart Citations
“…In this condition, the authors observed that matches had an energetic cost of approximately 181 kJ. As well as observed in karate matches [14,43], it was observed a predominance of the oxidative system (66%). When energy systems contribution was presented by each round it was observed an increase over time with an absolute oxidative contribution in round 1 (98 ± 15 kJ) lower than in rounds 2 (127 ± 14 kJ) and 3 (134 ± 18 kJ).…”
Section: Taekwondosupporting
confidence: 52%
“…As observed in jiu-jitsu, the aerobic metabolism solicitation to energy transfer during wrestling match also was quantified by HR, but a lesser number of studies and with less details can be found compared with modalities already above described. HR has been measured during a simulated competition, in a freestyle (5 matches in two days) [66], and Greco-roman style (5 matches in a unique day) [41] and in a single match [42,43].…”
Section: Wrestlingmentioning
confidence: 99%
See 1 more Smart Citation